Study of fluid-structure interaction on oscillating triangle wedge in water tunnel - Hazwan Amin. (2009)
This paper investigates the interaction of the fluid structure on the continuous oscillating equilateral triangle wedge in the uniform flow through dye flow visualization, phaseaveraged Particle Image Velocimetry (PIV) and force and torque measurements in the water tunnel. This particular fluid-structure interaction phenomenon is the continuous angular oscillation of a centrally-pivoted equilateral triangular cylinder, under uniform two-dimensional flow with initial perturbation. On the windward side of the cylinder, a vortex was formed at the sharp edges of the cylinder during the initial phase, whereas on the leeward side, the flow stayed attached. The phase-averaged Particle Image Velocimetry (PIV) measurements are also presented. PIV results show the interchange of flow patterns from that over a flat plate to flow past a sharp edge and vice versa as predicted. The PIV system used was DANTEC Dynamics ND-YAG. The wave length of this green light laser produced was 532 nm. The seeding particle was PSP Polyamide, 50 μm diameter. The software used for the PIV analysis was DANTEC DynamicStudio V1.45. An equilateral triangular cylinder of 30cm long and 10cm wide made up of plexiglass was used. The free-stream velocity was 16 cm/s. The period of the full oscillation cycle was 5.72 second. The corresponding Reynolds number based on width was 16000. Likewise, the Strouhal number was 0.108. The PIV plots shown were from the half-cycle (counter-clockwise motion) oscillation. The torque-angular position plot shows the stable oscillation manner. When the wedge moves in counter-clockwise motion (from +max to -max), the moment changes sign from positive to negative. The 4 initial moment is rather constant (~ + M0) until the wedge moves pass the equilibrium point ( = 0), the moment reduces to opposite value (-M0). At the -max position, the moment is negative, causing the wedge to move back (clockwise), i.e. -max to +max, and vice versa.